A VISUAL LANGUAGE DESIGN AS A NEW MEDIA FOR INCLUSIVE EDUCATION FOR STUDENTS WITH AUTISM SPECTRUM DISORDER (ASD) - Sonia, Candy; Hepi, Petrus (SEEIJ (Social Economics and Ecology International Journal), 2024)
The development of educational institutions in Indonesia and globally is currently facing the challenge of how to answer the needs of students diagnosed with Autism Spectrum Disorder (ASD) in receiving and understanding lecture materials, specifically designed in new media needs to be designed to facilitate and support the learning activities of ASD’s students and the goal of inclusive and sustainable education can be achieved. A visual research method was carried out with 4 stages of analysis, namely the image aspect, technical aspect, maker aspect and viewer aspect, then supported by statements from experts in designing the right visual language to convey the syllabus of the Digital Design Production (DDP) course. The result is that the right visual language will help students with ASD receive the message conveyed during the learning activities.